Improved MOF nanoparticle recovery and purification using crosslinked PVDF membranes - Van Goethem, Cédric; Mertens, Matthias; Cirujano, Francisco G; Seo, Jin W; De Vos, Dirk; Vankelecom, Ivo F J (Chemical communications (Cambridge, England), 2018)
Crosslinked PVDF-membranes are demonstrated to offer a viable alternative for centrifugation in the preparation of MOF-particles, thus realising new opportunities at lab-scale and continuous production at large-scale. The membranes combine extreme-pH with solvent stability, thus enabling application in any MOF synthesis, demonstrated here for ZIF-8, ZIF-67, HKUST-1, UiO-66 and MIL-53(Al).